Posted by **Cody** on Wednesday, May 19, 2010 at 8:17pm.

Simplify: (6y + 10z) - (13y - 5z + 4)

## Answer this Question

## Related Questions

- math help - Which is equivalent to 14x-3y+2z=100 -17x+8y+10z=11 -3+13y+29z=81
- Algebra, check. - 10z-4=10z-2 So I subtract 4 from the 2 right? and 10 from the ...
- Algebra - Simplify the following expression: 2(4y + 5z) - 10z
- algebra - does 13x^2+13y+8x^2 collect like terms =21x^2+13y
- Math - Simplify the following expression:2(4y + 5z) - 10z
- Math - Simplify the following expression:2(4y + 5z) - 10z
- Math - Please check my answers, which are at the bottom of each question...:) ...
- solution - 5y^2-13y+6 If you wish to factor, the factors are: (5y - 3)(y - 2) ...
- Math - Solve the system using any algebraic method. 2x - 2y + z = 3 5y - z = -31...
- math - 6. -2r(8r + 5) a -16r2 + 5 b -16r2 +10 c -16r2 -10r d -16r2 - 10 7. 4a (...